Dielectric behaviour of mechano-chemically synthesised [(CH3NH3)3Bi2Br9]: a lead free hybrid perovskite. (29th July 2022) - Pujaru, Swagatalaxmi; Sadhukhan, Priyabrata; Halder, Mithun; Ghosh, Basudev; Dhara, Arup; Das, Sachindranath
ABSTRACT: Lead-free hybrid halide perovskite (CH3 NH3 )3 Bi2 Br9 has been successfully synthesised by mechano-chemical method. The microstructure analysis by Rietveld's refinement method revealed that the crystal belongs to trigonal system with space group P 3 ˉ m 1. The obtained microstructural parameters are well in agreement with the previously published data. Temperature-dependent AC conductivity, impedance spectroscopy and complex dielectric properties have been investigated in detail. The negative temperature coefficient of resistance behaviour reveals the semiconducting nature of the materials. The complex impedance spectroscopy also supports the semiconducting nature of the sample with activation energy for conduction ~0.38 eV.